Technical Readiness and Facilitating Conditions Drive Electronic Medical Record Use Beyond Performance Expectations and Social Influence - Rokhmah, Erfina; Putra, Bayu Taruna Widjaja; Munawir, Al (FORIKES, 2026)
The acceleration of digital transformation in Indonesia’s health sector mandates the implementation of Electronic Medical Records (EMR) integrated with the SATUSEHAT platform. However, variations in healthcare workers’ readiness and acceptance remain a major barrier, particularly in outpatient units. This study aimed to analyze factors influencing behavioral intention and actual use of EMR based on the Unified Theory of Acceptance and Use of Technology (UTAUT). A quantitative explanatory survey with a cross-sectional design was conducted among 207 healthcare workers selected through proportionate stratified random sampling from a population of 438 outpatient staff across five type-C hospitals in Lumajang Regency. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The UTAUT constructs included performance expectancy, effort expectancy, social influence, and facilitating conditions, with age and experience as moderating variables. Effort expectancy and facilitating conditions significantly influenced both behavioral intention and EMR use, either directly or indirectly through intention. In contrast, performance expectancy and social influence showed no significant effects. Moderation analysis revealed that age weakened the effect of social influence on intention, while experience reduced the effect of facilitating conditions on usage behavior. The model explained 65.5% of the variance in intention and 37.8% in usage behavior. In conclusion, technical readiness and operational support play a more critical role in EMR adoption than perceived performance benefits or social influence. Strengthening infrastructure and user training is essential to support successful digital transformation in hospitals.Keywords: electronic medical records; behavioral intention; usage behavior